Capacitação de educadores em educação ambiental e educação patrimonial focada em recursos hídricos: fazenda-escola Fundamar (Paraguaçu/MG, baixo curso do rio Sapucaí) - Maria Lucia Prado Costa (2011)
This thesis presents a tool for the training of public elementary school educators in environmental and heritage education focused on water resources from an interdisciplinary perspective. The school in question is the Farm-School Fundamar, a project of the Third Sector entity: the March 18th Foundation in partnership with the Ministry of Education of Minas Gerais. The school is located in the municipality of Paraguaçu in southern Minas Gerais on the lower course of the river Sapucaí. As discussed previously in this dissertation, the present theme is the scope and limits of hybridization between environmental education and heritage education in legislation regarding the actors involved in the theme of water resources in Minas Gerais. It presents a critique of the main environmental education project focused on equity and water resources in the state. And from that critique, two complementary narratives are constructed using different methodologies: the history of the basins which extend over the community served by the farm-school Fundamar and the history of the watersheds of the Furnas Reservoir and the lower valley River Sapucaí. We tried to identify these narrative temporalities in which the river would carry the main role in their surroundings. The constructs of this background were implemented as a didactic tool for the training of educators, from the perspective of constructivist theory. It is a tool for in-service training by proposing activities for educators developing their students 7-16 years old, according to the profile of each group.